Robotic surgical skill acquisition: What one needs to know? - Akshay Sood; Wooju Jeong; Rajesh Ahlawat; Logan Campbell; Shruti Aggarwal; Mani Menon; Mahendra Bhandari (Journal of Minimal Access Surgery, 2015)
Robotic surgery has been eagerly adopted by patients and surgeons alike in the field of urology, over the last decade. However, there is a lack of standardization in training curricula and accreditation guidelines to ensure surgeon competence and patient safety. Accordingly, in this review, we aim to highlight ′who′ needs to learn ′what′ and ′how′, to become competent in robotic surgery. We demonstrate that both novice and experienced open surgeons require supervision and mentoring during the initial phases of robotic surgery skill acquisition. The experienced open surgeons possess domain knowledge, however, need to acquire technical knowledge under supervision (either in simulated or clinical environment) to successfully transition to robotic surgery, whereas, novice surgeons need to acquire both domain as well as technical knowledge to become competent in robotic surgery. With regard to training curricula, a variety of training programs such as academic fellowships, mini-fellowships, and mentored skill courses exist, and cater to the needs and expectations of postgraduate surgeons adequately. Fellowships provide the most comprehensive training, however, may not be suitable to all surgeon-learners secondary to the long-term time commitment. For these surgeon-learners short-term courses such as the mini-fellowships or mentored skill courses might be more apt. Lastly, with regards to credentialing uniformity in criteria regarding accreditation is lacking but earnest efforts are underway. Currently, accreditation for competence in robotic surgery is institutional specific.